Translation of the yeast transcriptional activator GCN4 is stimulated by purine limitation: implications for activation of the protein kinase GCN2. - Rolfes, R J (1993)
The transcriptional activator protein GCN4 is responsible for increased transcription of more than 30 different amino acid biosynthetic genes in response to starvation for a single amino acid. This induction depends on increased expression of GCN4 at the translational level. We show that starvation for purines also stimulates GCN4 translation by the same mechanism that operates in amino acid-starved cells, being dependent on short upstream open reading frames in the GCN4 mRNA leader, the phosphorylation site in the alpha subunit of eukaryotic translation initiation factor 2 (eIF-2 alpha), the protein kinase GCN2, and translational activators of GCN4 encoded by GCN1 and GCN3. Biochemical experiments show that eIF-2 alpha is phosphorylated in response to purine starvation and that this reaction is completely dependent on GCN2. As expected, derepression of GCN4 in purine-starved cells leads to a substantial increase in HIS4 expression, one of the targets of GCN4 transcriptional activation. gcn mutants that are defective for derepression of amino acid biosynthetic enzymes also exhibit sensitivity to inhibitors of purine biosynthesis, suggesting that derepression of GCN4 is required for maximal expression of one or more purine biosynthetic genes under conditions of purine limitation. Analysis of mRNAs produced from the ADE4, ADE5,7, ADE8, and ADE1 genes indicates that GCN4 stimulates the expression of these genes under conditions of histidine starvation, and it appeared that ADE8 mRNA was also derepressed by GCN4 in purine-starved cells. Our results indicate that the general control response is more global than was previously imagined in terms of the type of nutrient starvation that elicits derepression of GCN4 as well as the range of target genes that depend on GCN4 for transcriptional activation.